Evaluasi Program Implementasi Manajemen Mutu pada Politeknik Negeri Manado - Bernadain D Polii (Pedagogia: Jurnal Ilmiah Pendidikan, 2015)
The purpose of this study was to obtain information about evaluation of the implementation of a quality management program at Manado state Polytechnic. This study uses the Balanced Scorecard evaluation model that addresses four perspectives: customer perspective, learning and growth, internal business process perspective, a financial perspective. The analysis of a case study using qualitative and quantitative data. The process of data collection is through interviews, documentation, observations. The Results of the study are: (1) the customer’s perspective shows excellent status with indicators increasing satisfaction indicators of care, (2) perspective learning and growth perspective shows unfavorable status with indicators of empowerment and alignment of human resources, improving information system, (3) internal business process perspective shows the status indicator in not good with financial management system, research and community service, an increase in teaching and learning, (4) financial perspective with an indicator showing the status of both the optimization of the budget, and ability to raise founds. Performance Value Unit (NKU), which also serves as a status value indicates better performance leader although the need to make continuous improvement.